Incorporating CEFR bands and ICT-competences in grammar syllabuses of English Language Education Study Program in Indonesia - Siti Drivoka Sulistyaningrum; Purnawati Purnawati (Journal on English as a Foreign Language, 2021)
The incorporation of Information and Communication Technology (ICT) into the educational field has been widely implemented as 21st century skill. Common European Framework of Reference for Languages (CEFR) is one of the global standard languages required for global standard. However, in Indonesian context, there is lack of syllabuses incorporating CEFR bands and ICT-competences. This study explores the CEFR levels and ICT-competences incorporating in grammar syllabuses of ELESP in Indonesian universities. A content analysis method is used. Fifteen syllabuses of the grammar of the ELESP from 8 universities in Indonesia were selected purposely based on the proportion of private and public universities. All the grammar syllabuses are identified as Basic, Intermediate, and Advanced grammar. The findings revealed that: basic grammar, the CEFR level was A1-B1, intermediate grammar, the CEFR level was A1-B2, while the advanced grammar showed that CEFR level was B2-C2. In addition, the ICT-competences in entire syllabuses showed insufficient utilization which dominated Knowledge Acquisition and less intended for Knowledge Deepening and Knowledge Creation. These findings contribute as a reference to adjust and re-align the existing syllabuses to be in line with the CEFR bands framework and enriched with ICT-competencies.